Early human embryonic development: Blastocyst formation to gastrulation - Rossant, Janet; Tam, Patrick P.L. (Developmental cell, 2022)
There has been recent renewed interest in studying human early embryonic development. The advent of improved culture conditions to maintain blastocysts in vitro for an extended period and the emerging stem-cell-based models of the blastocyst and peri-implantation embryos have provided new information that is relevant to early human embryogenesis. However, the mechanism of lineage development and embryonic patterning, and the molecular pathways involved in their regulation, are still not well understood. Interest in human embryonic development has been reinvigorated recently given numerous technical advances. In this review, Rossant and Tam discuss new insights into human embryogenesis gathered from successes in culturing human embryos in vitro and stem-cell-based embryo models. Then they outline what questions still need answering.